Community Diagnosis of Knowledge, Attitudes, and Practices Towards COVID-19 Prevention in Koja, DKI Jakarta Province, Indonesia - Agus Sugiharto; Damar P. Susilaradeya; Reza Haryo Yudanto; Rasyad Khalifah; Anastasia Asmoro; Dian Aris Priyanti; Julietta Tantri (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Background: The spread of COVID-19 in Indonesia was happening rapidly. The DKI Jakarta Province was the province with the highest prevalence of COVID-19. Thus, all areas in DKI Jakarta Province require special attention in the spread of COVID-19, one of which is Koja District, North Jakarta. This study was conducted to find out community diagnoses related to knowledge, attitudes, and practices regarding COVID-19 prevention.Methods: This study uses community diagnostic steps and quantitative analysis with a cross-sectional approach. The study was conducted from May 26 until June 5, 2020. The population was 115 people who seek treatment at the Koja Health Center, North Jakarta. Socio-demographic characteristics, as well as knowledge, attitudes, and practices related to COVID-19 prevention, were collected through a self-reported questionnaire. Data analysis were used by IBM SPSS version 26.0.Results: Among 115 respondents, 58.3% had good knowledge, 64.3% had a positive attitude, and 55% had positive practices related to COVID-19 prevention. The median values of knowledge, attitudes, and practices are 8, 24, and 25. The median value of knowledge is higher than the mean value, and others are almost the same as the mean value. The percentage of correct knowledge is above 90%, except for knowledge about people infected with COVID-19 who are asymptomatic (64.3%) and children who cannot be seriously ill/die if exposed to COVID-19 (33.9%). More than half of the participants had positive attitudes and practices towards the preventive measures in question, except attitudes about family members at home having to keep their distance and wearing masks inside the house (48.7%) and practices about continuing to travel outside the house (36.5%).Conclusion: Community diagnosis in Koja District, North Jakarta, more than half of the community has a sufficient level of knowledge, positive attitudes, and practices towards COVID-19 prevention. These findings still require further intervention, so that people’s knowledge, attitudes, and practices regarding COVID-19 prevention are better, especially regarding children infected with COVID-19, the importance of keeping a distance and using masks at home, and traveling outside the home. So that the provision of education and counseling to the community is essential.